Time trends in the incidence and mortality of ovarian cancer in Ireland, Northern Ireland and Israel, 1994-2013 - HAYES, CATHERINE; Keinan-Boker, Lital; Silverman, Barbara G.; Walsh, Paul M.; Gavin, Anna T. (My University, 2017)
Objectives: The aims of this study were to compare time trends in ovarian cancer incidence and mortality in populations with (1) similar genetics but different health care systems (Ireland and Northern Ireland [NI]) and (2)different genetics but similar health care system (Israeli Jews and Arabs) and to interpret the results. Methods: Age-standardized rates of ovarian cancer incidence and mortality for 1994–2013 in the 3 countries were obtained from national cancer registries and national statistics. Time trends in incidence, mortality, and incidence-to-mortality ratio were assessed by linear regression models applied to each country and between populations (Ireland-NI, Ireland–Israeli Jews, Israeli Jews–Arabs). Joinpoint analysis was used to calculate the annual percentage change (APC). Results: Ovarian cancer incidence and mortality rates in 1994 were similar in the countries studied. Thereafter a reduction in incidence and mortality was observed in Ireland (incidence APC1994–2013 = −0.75%, P < 0.05; mortality APC1994–2013 = −0.67%, P < 0.05), NI (incidence APC1998–2013 = −1.5%, P < 0.05; mortality APC2005–2013 = −3.8%, P < 0.05), and Israeli Jews (incidence APC1994–2013 = −2.2%, P < 0.05; mortality APC1994–2013 = −1.2%, P < 0.05). Trends in Israeli Arabs remained stable. Significant incidence trend differences between Ireland and Israeli Jews (P = 0.009) and between Israeli Jews and Arabs (P = 0.004) were observed. The only significant trend difference for mortality was between Israeli Jews and Arabs (P = 0.038). Incidence-to-mortality ratios showed stable trends in all groups except for Israeli Jews (APC1994–2013 = −1.0%, P < 0.05). Conclusions: Time trends in ovarian cancer incidence (decreasing) and mortality (decreasing) were similar in Ireland, NI, and Israeli Jews, following global trends, with a more prominent incidence decline in Israeli Jews. Decreasing mortality trends are driven by falling incidence in the countries studied rather than improved survival.
PUBLISHED
Keywords: Incidence trends; Ireland; Israel; Mortality trends; Northern Ireland; Ovarian cancer; Cancer; Epidemiology